Expression of Ki-67 has Correlation with the Degree and Size of Endometriosis Cysts - Anwar, Ruswana; Alif, Muhammad; Pribadi, Adhi (Journal of Medicine and Health, 2015)
Endometriosis is one of the most common gynecological problem. Cells resulted in chronic inflammation and progressive, proliferative, invasive and even infiltrating an area that resembles the character of the malignancy. Ki-67 is an antigen on the cell nucleus that is found only in actively dividing cells. Expression of Ki-67 are associated with an aggressive tumor and metastasis. This study aims to determine the level of Ki-67 expression correlation with stage and size of the endometriosis cyst. Methods research is observational analytic cross cut method on 56 paraffin blocks of patients who have been diagnosed with endometriosis and had performed a laparotomy or laparoscopic surgery in Dr Hasan Sadikin Hospital. The results showed a significant relationship between the level of expression of Ki-67 with endometriosis cyst size (p <0.001) with a fairly strong relationship (0.55) according to statistics based on criteria Guilford. Moreover the results also showed a significant relationship between the level of expression of Ki-67 with endometriosis stage (p <0.001) with a fairly close relationship (0.564) according to statistics based on criteria Guilford. It can be concluded that the expression of Ki-67 associated with cyst size and stage of endometriosis.Â Keywords: Ki-67, endometriosis stage, endometriosis cyst